Bimetallic nanowires as electrocatalysts for nonenzymatic real-time impedancimetric detection of glucose - Mayorga Martinez, Carmen Clotilde (2012)
Gold-platinum nanowires are proposed as electrocatalysts for a real-time nonenzymatic impedancimetric detection of glucose. The electrochemical behavior of the obtained platform toward electrocatalytic oxidation of glucose, including a proposal for the detection mechanism, is shown. © The Royal Society of Chemistry 2012.